Odpowiedź :
Odpowiedź:
[tex]a)(1 \frac{1}{4} {)}^{3} =( \frac{5}{4} {)}^{3} = \frac{5}{4} \times \frac{5}{4} \times \frac{5}{4} = \frac{125}{64} [/tex]
[tex]b)(2 \frac{2}{3} {)}^{2} = ( \frac{8}{3} {)}^{2} = \frac{8}{3} \times \frac{8}{3} = \frac{64}{9} [/tex]
[tex]c)( - 1 \frac{1}{2} {)}^{3} = ( - \frac{3}{2} {)}^{3} = ( - \frac{3}{2}) \times ( - \frac{3}{2}) \times ( - \frac{3}{2}) = - \frac{27}{8} [/tex]
[tex]d)( - 2 \frac{2}{5} {)}^{2} = ( - \frac{12}{5} {)}^{2} = ( - \frac{12}{5}) \times ( - \frac{12}{5}) = \frac{144}{25} [/tex]